Prescribing cannabis for harm reduction - Collen Mark (BMC, 2012)
Abstract Neuropathic pain affects between 5% and 10% of the US population and can be refractory to treatment. Opioids may be recommended as a second-line pharmacotherapy but have risks including overdose and death. Cannabis has been shown to be effective for treating nerve pain without the risk of fatal poisoning. The author suggests that physicians who treat neuropathic pain with opioids should evaluate their patients for a trial of cannabis and prescribe it when appropriate prior to using opioids. This harm reduction strategy may reduce the morbidity and mortality rates associated with prescription pain medications.